Muscle regeneration after high-dose radiation exposure: therapeutic potential of Hedgehog pathway modulation?. (4th May 2022) - Rota Graziosi, E.; François, S.; Pateux, J.; Gauthier, M.; Butigieg, X.; Oger, M.; Drouet, M.; Riccobono, D.; Jullien, N.
Abstract: Purpose: Intentional or accidental exposure of relatively large as well as localized areas of the skin to ionizing radiation can lead to severe damage of many of its cellular components and cutaneous radiation syndrome. Patients can be treated with an invasive surgical procedure coupled with autologous cell therapy. However, this approach remains perfectible, especially for muscle repair. Indeed, a severe underlying muscle defect persists, in particular because of the damage to the satellite cells which ensure muscle regeneration. To overcome these shortcomings, a solution could be to develop new therapeutic strategies based on pharmacological treatments to improve post-irradiation muscle regeneration. In this study, we focus on the Hedgehog signaling pathway as a target, due to its involvement in myogenesis. Materials and methods: To evaluate the benefit of the pro-myogenic Hedgehog signaling pathway modulation, recombinant Sonic Hedgehog (rShh; agonist) or Cyclopamine (antagonist) were used in a stable cell line of mouse C2C12 myoblasts exposed to radiation (X-rays; 5 Gy). Our in vitro studies were carried out under either proliferation or differentiation conditions. Proliferation, migration, survival (apoptosis) and expression of myogenic genes/proteins were evaluated. Results: A high dose of radiation was shown to exert a serious negative impact in our in vitro model of mouse muscle progenitors after irradiation in proliferation or differentiation conditions. Interestingly, Hh pathway stimulation by rShh promotes the proliferation of myoblasts and their survival while its blockade by Cyclopamine significantly increases cell differentiation toward mature myotubes. Conclusion: These data suggest that, after irradiation, the sequence of activation and inhibition of the Hh pathway could allow rescue and proliferation of satellite cells, followed by their differentiation to regenerate new fibers. On the basis of these encouraging in vitro results, the second phase of our study will involve the in vivo validation of this treatment in a new murine model of ultra-localized muscle irradiation.